The case for a four-day week - Coote, Anna; Harper, Aidan; Stirling, Alfie (Polity, 2021)
"How a longer weekend can make us happier, healthier and greener"--
Enthält Literaturverzeichnis und Index
Keywords: Workweek; Quality of work life; Work-life balance; Time management; Flexible Arbeitszeit; Vereinbarkeit von Familie und Beruf; Arbeitszeitgestaltung